2019
DOI: 10.3390/ijms20102554
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bilastine on Diabetic Nephropathy in DBA2/J Mice

Abstract: Diabetic nephropathy is an unmet therapeutic need, and the search for new therapeutic strategies is warranted. Previous data point to histamine H1 receptor as a possible target for glomerular dysfunction associated with long term hyperglycaemia. Therefore, this study investigated the effects of the H1 receptor antagonist bilastine on renal morphology and function in a murine model of streptozotocin-induced diabetes. Diabetes was induced in DBA2/J male mice and, from diabetes onset (glycaemia ≥200 mg/dL), mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…In hypertension, increased mean arterial pressure (MAP) causes damage to cardiac and renal tissues, which results in the release of endogenous DAMPs. In turn, DAMPs, via activation of TLRs, may induce de novo histamine production or histamine release by infiltrating or resident immune cells, and ICV injection, 50 nmol (Jochem et al, 2016); IP injection, 20 mg/kg (Hattori et al, 2016) Protected slit diaphragm integrity in human immortalized podocytes in response to treatment with histamine (Veglia et al, 2016); reversed leptininduced rise in mean arterial pressure, heart rate, and renal blood flow in rat model of hemorrhagic shock (Jochem et al, 2016); reduced blood levels of IL-6, IL-1β, and TNF-α, reduced tissue levels of IL-1β, ILβ6, and TNF-α mRNAs, reduced levels of NGAL, serum BUN, and creatinine in mouse model of sepsis (Hattori et al, 2016) Rupatidine Antagonist 3.8 nM (IC50) Oral, 3 and 6 mg/kg/day in CMC Ameliorated diabetic nephropathy, improved histopathology, reduced fibrosis, and senescence markers in a rat model of streptozotocin-induced diabetes (Hafez et al, 2020) Bilastine Antagonist 64 nM (IC50) Oral gavage in water solution, 1-30 mg/ kg Prevented the increase in ACR, restored creatinine clearance, and preserved junctional integrity in a rat model of streptozotocin-induced diabetes (Verta et al, 2019) Ketotifen Antagonist 1.3 nM (Ki) IV injection, 1 mg/kg (Tong et al, 2016); IP injection, 1 mg/kg/day in 0.5% CMC (Reena et al, 2016) Reduced histological injury score, BUN serum creatinine, IL-6, and TNFα, downregulated expression of ICAM-1, increased activity of SOD, in renal tissues in I/R rat model (Tong et al, 2016); attenuated HFD induced increase in body weight, kidney weight to body weight ratio, and in renal parameters (decrease in serum creatinine, increased levels in BUN, uric acid, K + , and microproteinuria, increase in systolic blood pressure), reversed HFD induced morphological changes in a HFD-fed model in rats (Reena et al, 2016) Mirtazapine Antagonist…”
Section: Effects Of Histamine On Renal Physiology and Pathophysiologymentioning
confidence: 99%
“…In hypertension, increased mean arterial pressure (MAP) causes damage to cardiac and renal tissues, which results in the release of endogenous DAMPs. In turn, DAMPs, via activation of TLRs, may induce de novo histamine production or histamine release by infiltrating or resident immune cells, and ICV injection, 50 nmol (Jochem et al, 2016); IP injection, 20 mg/kg (Hattori et al, 2016) Protected slit diaphragm integrity in human immortalized podocytes in response to treatment with histamine (Veglia et al, 2016); reversed leptininduced rise in mean arterial pressure, heart rate, and renal blood flow in rat model of hemorrhagic shock (Jochem et al, 2016); reduced blood levels of IL-6, IL-1β, and TNF-α, reduced tissue levels of IL-1β, ILβ6, and TNF-α mRNAs, reduced levels of NGAL, serum BUN, and creatinine in mouse model of sepsis (Hattori et al, 2016) Rupatidine Antagonist 3.8 nM (IC50) Oral, 3 and 6 mg/kg/day in CMC Ameliorated diabetic nephropathy, improved histopathology, reduced fibrosis, and senescence markers in a rat model of streptozotocin-induced diabetes (Hafez et al, 2020) Bilastine Antagonist 64 nM (IC50) Oral gavage in water solution, 1-30 mg/ kg Prevented the increase in ACR, restored creatinine clearance, and preserved junctional integrity in a rat model of streptozotocin-induced diabetes (Verta et al, 2019) Ketotifen Antagonist 1.3 nM (Ki) IV injection, 1 mg/kg (Tong et al, 2016); IP injection, 1 mg/kg/day in 0.5% CMC (Reena et al, 2016) Reduced histological injury score, BUN serum creatinine, IL-6, and TNFα, downregulated expression of ICAM-1, increased activity of SOD, in renal tissues in I/R rat model (Tong et al, 2016); attenuated HFD induced increase in body weight, kidney weight to body weight ratio, and in renal parameters (decrease in serum creatinine, increased levels in BUN, uric acid, K + , and microproteinuria, increase in systolic blood pressure), reversed HFD induced morphological changes in a HFD-fed model in rats (Reena et al, 2016) Mirtazapine Antagonist…”
Section: Effects Of Histamine On Renal Physiology and Pathophysiologymentioning
confidence: 99%
“…The lack of effect on CrCl could also be explained by the purely tubular localization of the H 4 receptor being absent at the glomerular level [18]. Consistently, in vitro [36] and in vivo [61,62] data suggested that among the histamine receptors, the H 1 receptor is the one directly involved in hyperfiltration.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, there were clear signs of hypocellularity and proinflammatory cell infiltration [8]. However, it has to be noticed that the studies used different animal strains: DBA2/J [8,62] in the previous, and C57BL6J in this new study. The two strains have different susceptibility to diabetic nephropathy and to STZ, and differ in some renal pathological changes [63,64].…”
Section: Discussionmentioning
confidence: 82%
“…Bromfenac is also an excellent option as a lead molecule due to its highest predicted pEC50 value. Bilastine and bromfenac are drugs of interest to treat diabetes-related diseases [72,73]. In vivo studies suggested bilastine as therapy for diabetic nephropathy, a common microvascular complication in patients diagnosed with diabetes mellitus [72].…”
Section: Molecular Dynamic Simulationsmentioning
confidence: 99%
“…Bilastine and bromfenac are drugs of interest to treat diabetes-related diseases [72,73]. In vivo studies suggested bilastine as therapy for diabetic nephropathy, a common microvascular complication in patients diagnosed with diabetes mellitus [72]. Clinical trials reported the long-term benefits of bromfenac treating diabetic macular edema, a cause of loss of vision in patients with diabetes [73].…”
Section: Molecular Dynamic Simulationsmentioning
confidence: 99%